Improving Service Quality in a Tutoring Institutions using Fuzzy-Servqual - Febrian Krisnawati; Ardhianiswari Diah Ekawati (Universitas Mercu Buana, 2025)
Quality improvement is a business strategy that emphasizes fulfilling consumer desires. This study aims to determine consumer needs, in this case students, as a reference for improving the business quality of tutoring institutions by using the Fuzzy-Servqual method to sort out service quality values that can be used to determine priority handling. The evaluation criteria are determined based on the five dimensions of the servqual model. Fuzzy-servqual is applied to get the importance weight of each servqual model criterion. The dimension of physical evidence (tangibles) is a priority that needs to be evaluated, with a gap value of -0.08. The top priority is Availability of Green Areas -0.51, followed by Completeness, comfort and cleanliness of the library -0.44, and Comfort, cleanliness and safety of study rooms -0.24. The conclusion obtained is that the application of Fuzzy Servqual can be applied to measure the quality of service in a tutoring institution based on predetermined indicators. Future research should adopt a more comprehensive approach by considering various perspectives for a thorough understanding of improving the quality of services in tutoring institutions